REFORMASI PERUBAHAN PIDANA MENJADI TUNTUTAN DEMOKRASI PENEGAKAN HUKUMAN - M. Yusuf DM; Ridho Alfian Syahputra; Reymon Basir; Wira Adi Kusuma; Buyung Ganti; Muhammad Habib Kevin Setiyawan (LPPM STIH Awang Long, 2025)
Criminal law reform in Indonesia has emerged as a pressing demand in line with the development of democratic principles and the need to enforce the law fairly and effectively. Changes in the criminal justice system are not merely adjustments to legal norms but also reflect society’s aspirations for justice, the protection of human rights, and the accountability of law enforcement authorities. This article analyzes the direction of criminal law reform, emphasizing the importance of democratizing law enforcement processes, including the modernization of criminal regulations, the application of the due process of law principle, and the enhancement of judicial institutions’ roles in ensuring legal certainty and protecting individual rights. Criminal law reform in Indonesia also requires an evaluation of law enforcement procedures that have historically been repressive and less responsive to democratic principles. This includes revising criminal laws, strengthening oversight mechanisms for law enforcement officers, and implementing a restorative justice approach that emphasizes both offender rehabilitation and victim recovery. The study shows that democratizing criminal law enforcement requires not only legislative changes but also a shift in legal culture, increased transparency, and public participation in the legal process. Moreover, this article highlights challenges arising in criminal law reform, such as bureaucratic resistance, disparities in access to justice, and potential conflicts between security needs and the protection of individual rights. Addressing these challenges requires comprehensive strategies, including legal education for the public, professional training for law enforcement officers, and the strengthening of independent oversight institutions. The overall process of criminal law reform based on democratic principles is expected to enhance the legitimacy of the criminal justice system, reduce crime rates, and create a more just and civilized society.